Peran Kepemimpinan dalam Mewujudkan Key Performance Indicator di Sekolah XYZ, Jakarta Utara - Mesra (Magister Teknologi Pendidikan Fakultas Pascasarjana Pendidikan Universitas Pelita Harapan, 2024)
KPI (Key Performance Indicator) in XYZ school is specifically designed to improve the quality. This research studies the role of leadership in realizing KPI at XYZ School, North Jakarta. In detail, the research aims are: 1) to study the principal’s leadership in kindergarten, elementary, middle and high school in realizing KPI, 2) to study how the vice principals’ perception towards the leadership of the principal in realizing KPI. The research subjects are (i) principal (ii) three vice-principals (representing each level of education). All data from this study were collected from interviews. The data was then analyzed qualitatively using the triangulation method. The research findings in this study are: 1) principal applied situational and transformational leadership styles, meetings with school principals and encouraged the performance of deputy principals with a sense of friendliness, close, and consideration in realizing KPIs, 2) the vise pricipals have a good perception of principal’s leadership in realizing KPI.